Adjektiva pada Artikel Berita Lokal Papua dan Nasional Terkait Tragedi Kekerasan Kiwirok 13 September 2021 - Kurniawati, Yenny; Wijana, I Dewa Putu (Kajian Bahasa dan Sastra (KABASTRA), 2022)
This study aims to find out the ideological differences between the local Papuan online news media (Jubi.co.id) and the Indonesian national online news media (Kompas.com) with the highest reader traffic related to the news on the Kiwirok violence on September 13th, 2021, involving the TPNPB OPM and the Indonesian military. Media ideology is revealed by looking at the use of adjectives in news texts. This research uses the Fairclough model of Critical Discourse Analysis framework with Halliday's Systemic Functional Lingustics approach. The method of data collection was done by using purposive sampling documentation technique. The data is collected in a corpus to be processed with the Antconc. Adjective words are collected to be understood in the context of their use. The results showed that the media Jubi.co.id reports events by giving a bad image to the two parties: the party who carried out the attack and the state/ apparatus. Kompas.com reports the news by giving a bad image to the party who carried out the attack and a good image to the state/ apparatus.